Cleanliness preference behind the choice of drinking water at home: an analysis of online survey results in the Tokyo area. (23rd November 2021) - Suzuki, Koji
Abstract: Do different degrees of cleanliness preference affect consumers' choice of daily drinking water at home? The purpose of the present paper is to test the validity of various hypotheses related to this question by analyzing the results of an online survey conducted in the Tokyo area. Cleanliness has an aspect of personal norm for normalcy of things. Preference of cleanliness can be divided into the following two types. One is orderly cleanliness and the other is aversive cleanliness. Orderly cleanliness is oriented toward the control of impure things, while aversive cleanliness is oriented toward retention of immaculacy. We demonstrate that each of these cleanliness preference is involved in the choice of drinking water in its own way. Our survey results suggest that orderly cleanliness encourages the choice of tap water filtered through water purifier, while aversive cleanliness urges the choice of bottled water. HIGHLIGHTS: Orderly cleanliness urges the choice of tap water filtered through a water purifier. Orderly cleanliness urges the choice of bottled water. Aversive cleanliness inhibits the choice of untreated tap water. Aversive cleanliness urges the choice of bottled water.